Determination of metoprolol tartrate as Cu(II)dithiocarbamate complex - Alpdogan, G; Sungur, S (TAYLOR & FRANCIS INC, 1997)
An HPLC method has been developed for the determination of the beta adrenergic blocking drug metoprolol tartrate. The method is based on the formation of a Cu(II)-dithiocarbamate complex by precolumn derivatization of secondary amino group of metoprolol with CS2 and CuCl2 in the presence of ammonia. The complex is extracted into chloroform and injected into the chromatograph. Chromatographic separation was performed by a RP (mu Bondapak C-18) column with methanol - pH 5.8 phosphate buffer(80:20) as the isocratic mobile phase. A variable wavelength absorbance detector (lambda = 275 nm) was used A linear relationship was obtained between peak areas and metoprolol tartrate concentrations over the range of 35 - 180 nmol ml(-l). The method was applied to the analysis of metoprolol tartrate tablets and the results were statistically compared with those obtained by official method using t - and F - tests.
Keywords: metoprolol tartrate; Cu(II)-dithiocarbamate complex; high pressure liquid chromatography; tablets; CHROMATOGRAPHY; Chemistry